The effects of transportation on wheat prices to local Kansas wheat farmers - DeGroot, Shayna (Kansas State University, 2024)
Wheat farmers in Kansas play a critical role in helping feed the world. They work under volatile conditions that are unpredictable each year such as weather, basis, prices and yield. There are many factors that play into the volatility, specifically for basis prices, like transportation. This can be affected by the price of diesel, rail, ocean freight and futures price. While diesel is a major transportation input on farm operations and in grain transport, costs such as ocean freight and rail for exported commodities can be overlooked. Ocean freight plays a factor as roughly 50% of the wheat grown in Kansas is exported. The goal of this thesis is to examine how prices of diesel, rail, ocean freight and futures affect wheat basis for local wheat farmers across Kansas. The data for this study were collected from AgManager.info, the United States Department of Agriculture Agricultural Marketing Service, the United States Energy Information Administration and the Federal Reserve Economic Data. Data were collected as monthly averages from 2015 to 2023, a nine-year span, which included diesel prices, rail tariff rates, ocean freight rates, wheat futures prices and basis from elevators across Kansas including 21 towns from three counties in each of the seven agriculture districts. Elasticity has some variability across the models. Combining all seven districts, results indicated that on average, a 1% increase in futures would result in a 0.47% decrease in basis, a 1% increase in ocean freight would result in 2.47% increase in basis, a 1% increase in diesel would result in a 0.89% decrease in basis and a 1% increase in rail would result in a 0.12% increase in basis. Farmers should look at futures price, ocean freight, local diesel price and rail tariff rate before making decisions at elevators as all four factors affect wheat basis, with futures and diesel commonly decreasing basis and ocean freight and rail tariff rates commonly increasing basis. By looking at these factors, it will help farmers determine whether to sell their wheat or wait.
Keywords: Wheat; Basis; Transportation; Wheat basis; Futures prices